Bandgap Engineering of Ternary ε‐InSe1−xSx and ε‐InSe1−yTey Single Crystals for High‐Performance Electronics and Optoelectronics. Issue 13 (20th April 2022) - Hao, Qiaoyan; Yi, Huan; Liu, Jidong; Wang, Yi; Chen, Jiewei; Yin, Xinmao; Tang, Chi Sin; Qi, Dianyu; Gan, Haibo; Wee, Andrew T. S.; Chai, Yang; Zhang, Wenjing
Abstract: Alloying offers an efficient strategy to tune the bandgap of two‐dimensional (2D) layered materials, enabling them to tailor the optical and electronic attributes without compromising the structural integrity. Here the authors report the synthesis of a series of ternary InSe1− x S x and InSe1− y Te y alloys possessing ε‐polymorph and single crystalline structure. Both the photoluminescence and Raman spectra of multilayer InSe1− x S x and InSe1− y Te y demonstrate that an effective modulation of bandgap and concomitant optical properties is achieved by tuning the alloy compositions, consistent with density functional theory calculations. Field‐effect transistors fabricated from the multilayer alloys on SiO2 dielectric substrates display electron field‐effect mobilities of up to ≈127 cm 2 V −1 s −1 . All the multilayer alloy devices show a high current on/off ratio of ≈10 8 . When fabricated into photodetectors, multilayer InSe0.9 S0.1 and InSe0.9 Te0.1 exhibit maximum photoresponsivities of 5.4 × 10 5 and 7.7 × 10 4 A W −1, respectively. Moreover, the InSe1− y Te y alloys are able to expand the photoresponse range into 1250 nm due to the bandgap narrowing upon Te alloying. This work sheds light on rationally designing 2D layered InSe with tunable bandgaps via alloying, and demonstrates their promising applications in electronics and optoelectronics. Abstract : This paper reports an alloying strategy to prepare single crystals of InSe1− x S x and InSe1− y Te y with continuously tunable bandgaps. The ternary alloys are fabricated into field‐effect transistors, exhibiting competitive electronic and optoelectronic performance. This work provides additional degree of freedom for tuning the optical and electrical properties of InSe, and illustrates their potential applications in high‐performance electronic and optoelectronic devices.